2006
DOI: 10.2134/jeq2005.0151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use on Soil Inorganic Carbon Stocks in the Russian Chernozem

Abstract: Little is known about changes in soil inorganic carbon (SIC) stocks with depth and with land use in grassland ecosystems. This study was conducted to determine SIC stocks under different management regimes in the Mollisol, one of the typical soils in grasslands. Four sites were sampled: a native grassland field (not cultivated for at least 300 yr), an adjacent 50-yr continuous fallow field, a yearly cut hay field in the V.V. Alekhin Central-Chernozem Biosphere State Reserve in the Kursk region of Russia, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 11 publications
7
66
0
1
Order By: Relevance
“…Further, some recent studies calculated SIC as the difference between soil total carbon (STC) and SOC (e.g. Yang et al, 2010a;Mikhailova and Post, 2006). However, the proportions of carbonates in soil total carbon are usually small (Chatterjee et al, 2009), thus this method without the direct measurement of SIC could produce a large relative error.…”
mentioning
confidence: 99%
“…Further, some recent studies calculated SIC as the difference between soil total carbon (STC) and SOC (e.g. Yang et al, 2010a;Mikhailova and Post, 2006). However, the proportions of carbonates in soil total carbon are usually small (Chatterjee et al, 2009), thus this method without the direct measurement of SIC could produce a large relative error.…”
mentioning
confidence: 99%
“…grasses compared with annual crops have been known [22,25,26,29]. Increased STC at lower depths under perennial grasses and annual spring wheat was probably a result of presence of large amount of SIC in subsoil layers, as soils under dryland cropping systems in arid and semiarid regions are enriched with SIC, especially in the underlying layers [37,40]. Increased STC or SOC in underlying soil layers is beneficial for soil C sequestration, as SOC in subsoils is mineralized less than in the surface soil due to reduced microbial activity [25,26].…”
Section: Tablementioning
confidence: 99%
“…Drylands occupy 47% of the earth's total surface [38] where potential for C sequestration is substantial [39]. As management practices can influence STC, SOC, and SIC [36,36,40], using STC for measurement of total soil C sequestration instead of SOC due to management practices can substantially reduce the cost of analyzing soil samples, especially in arid and semiarid regions, because it eliminates the analysis of SIC [37]. Bronson et al [18] found that STC and STN were 11.0 Mg C ha −1 and 0.6 Mg N ha…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are critical for biofuel production since they affect fossil fuel inputs via nitrogen fertilizers [17], potential emissions of greenhouse gases such as nitrous oxide that counteract the greenhouse gas benefits of reduced carbon emissions [18], water quality and ecosystem services [19], and energy and economic feasibility [20]. Along with organic carbon sequestration, the long cultivation history (>100 years), continuous monoculture [21], and extensive soil amendments may have created conditions for inorganic carbon sequestration or emissions [22] in Hawaiian sugarcane soils that warrant examination. Furthermore, soil organic matter (SOM) is involved in the maintenance of soil quality, sustainability of natural and agricultural systems and the natural balance of greenhouse gases [23].…”
Section: Introductionmentioning
confidence: 99%